STATUS OF AN UZBEK LANGUAGE. NATIONAL LITERATURE OF UZBEKISTAN AND ITS REPRESENTATIVES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides a comprehensive overview of the status and significance of Uzbek language and literature within the cultural landscape of Uzbekistan. It traces the historical development of the Uzbek language from its ancient roots to its modern form, highlighting its role as a symbol of national identity and unity. Additionally, the article explores the evolution of Uzbek literature through different historical periods, from the classical era to the contemporary age. It discusses notable literary figures, their contributions, and the themes prevalent in Uzbek literature. Furthermore, the article emphasizes the importance of preserving and promoting Uzbek language and literature for future generations, underscoring their cultural, social, and historical significance